EFFECTIVENESS OF INSECTICIDES IN PROTECTING POTATOES FROM COLORADO POTATO BEETLE - Zaviriukha , П. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
During 2022–2023, studies were conducted at the experimental field of the Department of Genetics, Breeding, and Plant Protection of Lviv National Environmental University, located in the Western Forest-Steppe zone of Ukraine. The research focused on evaluating the effectiveness of various insecticides in protecting potato crops from the Colorado potato beetle. Three insecticide preparations were tested: 1. Koragen 20% - a suspension concentrate applied at a rate of 60 ml/ha. 2. Confidor Maxi 70% - water-soluble granules applied at a rate of 50 g/ha. 3. Aktara 25% - water-soluble granules applied at a rate of 60 g/ha. A control group was established with no insecticide application. The research included four potato varieties of different maturity groups, all of which are included in the State Register of Plant Varieties of Ukraine: - Bellarosa (early-ripening) - Vodohrai (mid-early) - Volia (mid-ripening) - Zahidna (mid-late). The results indicated that the new generation insecticides, Confidor Maxi 70% and Koragen 20%, demonstrated high technical efficiency, with effectiveness ranging from 88.2% to 89.4% for Confidor Maxi and 78.2% to 81.2% for Koragen, regardless of the potato variety. The data showed that the level of potato yield was influenced both by the biological characteristics of each variety and by the specific type of insecticide used. On average, over the two-year study period, the potato varieties treated with the systemic insecticide Confidor Maxi 70% produced the highest tuber yields as follows: - Bellarosa: 29.1 t/ha - Vodohrai: 30.4 t/ha - Volia: 33.8 t/ha - Zahidna: 30.9 t/ha. Conversely, the yields from the use of Aktara 25% were significantly lower: - Bellarosa: 25.6 t/ha - Vodohrai: 26.9 t/ha - Volia: 28.6 t/ha - Zahidna: 27.5 t/ha. For reference, the control group yields were markedly lower at: - Bellarosa: 8.6 t/ha - Vodohrai: 11.5 t/ha - Volia: 12.5 t/ha - Zahidna: 11.9 t/ha. To protect potato crops from the Colorado potato beetle in the Western Forest-Steppe zone, it is recommended to use Confidor Maxi 70% at a rate of 50 g/ha and Koragen 20% at a rate of 60 ml/ha. To mitigate the potential development of resistance in pests, it is suggested to alternate the use of these insecticides and to apply them in tank mixtures with recommended fungicides.